Bigger change faster: Integrated development, health and environment actions for a sustainable future - Goldstein, Joshua; Tallis, Heather; Linou, Natalia; Small, Roy; Ringler, Claudia; Bernal, Luisa; Bok, Ludo; Bryan, Elizabeth; Chao, Verania; Cooper, Simon; Zhang, Wei (Bridge Collaborative, 2019)
Achieving the Sustainable Development Goals and the pledge of the 2030 Agenda to leave no one behind requires collaborative ways of working, such accelerating and scaling cross-sectoral action and policy coherence. Today’s development challenges, including those related to the climate crisis, environment and health, are complex and interwoven. They demand holistic and integrated solutions that address multiple angles, engage diverse partners, and reach the people and places most in need with high-impact solutions. This premise is the impetus of this joint report by the Bridge Collaborative and UNDP “Bigger Change Faster: Integrated Development, Health, and Environment Actions for a Sustainable Future”. In line with UNDP’s ‘Strategic Plan 2018–2021’ and ‘HIV, Health and Development Strategy 2016–2021: Connecting the Dots’, UNDP supports countries to respond to complex development challenges in three inter-connected areas: (1) reducing the inequalities that drive illness; (2) effective and inclusive governance for health and (3) building resilient and sustainable systems for health. The report examines three large-scale sustainable development challenges for which cross-sector solutions are essential to accelerate and maximize progress towards the SDGs, the Paris Agreement, and other global commitments. These are (1) accelerating a low-carbon, clean air, and environmentally-friendly energy future for all; (2) transforming the global food system for health and sustainability and (3) targeting sanitation and wastewater improvements to benefit people and nature. The report is unique in its focus on achieving multiple benefits that do not miss key drivers or hinder progress on other development goals. It highlights that adopting a broader view and scaling up implementation of effective cross-sector actions to address these challenges can drive holistic progress across the SDGs.